The Perils of Technology: Social Networking Addiction and Anxiety - Roomana Zeb, Saima Arzeen, Momina Mumtaz, Maimoona Haroon (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: After the invention of smart phone with many social networking sites, young generation specially seems likely to be affected with its excessive use. Along with the benefits brought by changes in technology, some negative repercussions can also result. Keeping this in mind the aim of this study was to explore the association between anxiety and social networking addiction in young adults. Method: For the said purpose a convenience sample of 200 young adults from Peshawar with an equal distribution of males (n=100) and females (n=100) participated in the study. Correlational research design was used to conduct the research. Social Networking Addiction Scale (SNAS; Mumtaz, 2014) and the Beck Anxiety Inventory (BAI; Beck & Steer, 1990) were applied on the sample. Findings: Results revealed a significant positive correlation between social networking addiction and anxiety among university students. Additionally, one-way ANOVA indicated significant differences in anxiety levels between addicted and non-addicted social media users, while no significant differences were found between excessive and addicted users. The findings also suggested a higher prevalence of social networking addiction among females as compared to males. On the basis of the results it is concluded that excessive use of social networking sites can put individuals at risk of developing anxiety. Hence, the software developers should program the sites such that it should turn off after a due time. Similarly, parents of young children should control the screen time of their offspring. Keywords: Social networking addiction, anxiety, young adults, internet, gender differences.